THE ROLE OF GATA3, FOXA1, ELF5 TRANSCRIPTION FACTORS IN THE PATHOGENESIS AND PROGNOSIS OF BREAST CANCER - D. V. Vasilchenko; N. V. Krakhmal; S. V. Vtorushin; M. V. Zavyalova (Сибирский онкологический журнал, 2020)
Purpose of the study: to review available data on the role and significance of GATA3, FOXA1 and ELF5 transcription factors in the pathogenesis, progression and therapy resistance of breast cancer.Material and Methods. The Medline and PubMed databases were used to identify all studies that evaluated the structure, functional parameters and participation of the studied transcription factors in the pathogenesis of breast cancer. More than 180 publications were analyzed, of which 76 were included into the review.Results. The review shows that molecular genetic studies in relation to transcription factors and subsequent comparison of the obtained results with various clinical and morphological characteristics of breast cancer are of great importance. The review also demonstrates the inconsistency of the available data regarding clinical significance in assessing the prognosis of the disease and the sensitivity of the tumor to hormone therapy.Conclusion. The study of the expression parameters of GATA3, FOXA1, and ELF5 transcription factors, as well as their relationship with tumor progression mechanisms will increase the reliability of immunomorphological studies, most likely suggesting the efficiency of hormone therapy. Therefore, the results of this study can help to plan adequate treatment tactics and predict outcomes in patients with breast cancer.